Development and quality assessment of a functional dairy and vegetable product - K. R. Babukchadiya; A. O. Ermolaev; V. S. Podtoptanny (Новые технологии)
The article is devoted to the development of the production technology of a dairy and vegetable product with functional properties with established optimal dosages of enriching components. The article presents a comparative analysis of the chemical composition and properties of enriching components in the form of pumpkin of the Kroshka variety, Lavitol-arabinogalactan and flower honey, and substantiates the possibility of enriching curd products with β-carotene, dietary fiber, vitamins and minerals. The method for obtaining powder from pumpkin pulp with a particle size of about 0.5 mm has been established. The authors have studied the influence of the selected enriching additives on the quality characteristics of the developed curd product. As a result of the combination of dairy and vegetable components, the curd mass «Solnyshko» – a product with high nutritional and biological value has been obtained. The main value of the developed curd mass lies in the ability to provide the body with beta-carotene and dietary fiber. The optimal ratios of prescription components in the developed «Solnyshko» curd mass have been established in the following ratios: cottage cheese (WFF 9%) – 86.11%, pumpkin pulp powder – 5%, flower honey – 6.39%, Lavitol-arabinogalactan – 2,5%. The developed curd product has a high nutritional value. It has been determined that consumption of 100 g of «Solnyshko» curd mass will satisfy the daily physiological need for beta-carotene by 63.6%, for dietary fiber – by 18.4%. The shelf life of the enriched curd mass is 10 days at a storage temperature of 4±2℃. Industrial testing of the «Solnyshko» curd mass technology was carried out at the «Line» LLC PСС (Blagoveshchensk, the Amur Region).